Mode of delivery preferences: the role of childbirth fear among nulliparous women - Elgzar, Wafaa Taha; Alshahrani, Majed Saeed; Ibrahim, Heba Abdel-Fatah (Frontiers in Psychology, 2023)
The increasing Cesarean Section (CS) rates may be attributed to women's increasing requests for elective CS. High Fear of Childbirth (FOC), especially among nulliparous women, may be significantly associated with CS preference without medical indications. The current study aims to investigate the impact of childbirth fear on the mode of delivery preference among nulliparous women. A cross-sectional correlational study was performed in the Maternal and Children Hospital (MCH) from the beginning of October 2022 to the end of February 2023 and incorporated a convenience sample of 342 nulliparous women. The data was collected using a self-reported questionnaire comprising participants' demographic and obstetrics characteristics and the FOC questionnaire. A logistic regression model examined the relationship between CS preference and the other independent variables. The results indicated that 74.3% of the nulliparous women preferred vaginal delivery, while 25.7% preferred cesarean section. Concerning childbirth-related fear, the highest mean scores were related to fear of clinical procedures, fear of harming or distressing the infant, and fear of pain 5.19±1.13, 5.12±1.27, and 5.09±1.22, respectively. High FOC was present among 74.6%, moderate in 17.3%, and severe in 6.7% of the participants. Logistic regression analysis showed maternal age and monthly income were the significant sociodemographic determinants of choosing CS as the preferred delivery mode (p <0.05). Moreover, the participants who had increased fear of harming or distressing the infant, fear from pain, fear from the body's ability to give birth, fear from not being involved in decision-making, and overall FOC had a higher probability of choosing CS as the preferred delivery mode compared to the participants who had lower fear (p <0.05). Conclusion: Having high FOC increases the CS preference among nulliparous women. Increased fear of harming or distressing the infant, fear from pain, fear from the body's ability to give birth, and fear from not being involved in decision-making seem to be significant dimensions of childbirth fear associated with CS preference among nulliparous women.